Characteristic Of Demographic Neuropathy Diabetic Perifer In The Agriculture Area - Ana Nistiandani; Lantin Sulistyorini; Muhammad Fakhurur Rozsy; Nuril Fauziah (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2019)
Jember Regency is a superior area in the agricultural sector, but it is contrary to the health conditions of the people. It was noted that Jember experienced an increase in cases of Diabetes Mellitus (DM). DM causes various complications, one of which often occurs is peripheral neuropathy. This study aims to analyze peripheral neuropathy based on the characteristics of people with diabetes in the agriculture area under the auspices of the Health Department of Jember Regency. This type of research is descriptive with the cross-sectional approach. The sampling technique used is total population sampling. The number of respondents in this study was 102 people with diabetes. The instrument used was a modification of the MNSI (Michigan Neuropathy Screening Instrument) and MDNS (Michigan Diabetic Neuropathy Score). Univariate analysis is performed, which is presented in the form of frequency distribution tables and cross-tabulation. The results of this study indicate that all respondents experienced peripheral neuropathy (100%) in the mild (43.1%), moderate (44.2%), and severe (12.7%) categories. Domination of neuropathy by women (53.9%), has comorbidities (68.6%), middle adult age categories (71.6%), blood sugar levels 90-199 mg/dL (57.8%), and duration of DM ≥ 1 to 5 years (58.8%). A small percentage of people with diabetes who have peripheral neuropathy have a history of DFU (9.8%) and a history of smoking (32.4%). This nursing intervention is needed to prevent worsening of peripheral neuropathy.